Clinical and analytical monitoring of patients with multiple sclerosis on anti-CD20 therapeutics: a real-world safety profile study - Fernandes, André Aires; Neves, Ana Lídia; Ferro, Daniela; Seabra, Mafalda; Mendonça, Teresa; dos Reis, Ricardo Soares; Sá, Maria José; Guimarães, Joana; Abreu, Pedro (Frontiers in Neurology, 2025)
BackgroundAnti-CD20 monoclonal antibodies are a class of immunosuppressive drugs widely used in the treatment of central nervous system (CNS) inflammatory diseases, with well-established efficacy and safety. Although rare, these therapies can be associated with serious adverse events including hematological and infectious complications. This study aims to evaluate their safety and tolerability profile in real-world clinical practice.MethodsWe conducted a retrospective cohort study comprising patients diagnosed with multiple sclerosis (MS) treated with anti-CD20 drugs since 2016 followed in the Demyelinating Diseases clinic of a tertiary center. Clinical and paraclinical parameters were evaluated, including complete blood count and immunoglobulins measurements.ResultsA total of 160 with multiple sclerosis (pwMS) were included in our study, of whom 110 (68.8%) were female and 147 are currently receiving anti-CD20 therapies. Half of the patients were diagnosed with relapsing–remitting MS, while the remaining had progressive forms, including 23 with primary-progressive MS and 57 with secondary-progressive MS. Eighty-three patients were on ocrelizumab, 48 on rituximab, and 29 on ofatumumab. The mean follow-up duration from the start of anti-CD20 therapy was 30.5 ± 21.3 months. During this period, serious adverse events were observed in 9 patients, including SARS-CoV-2 infection (resulting in one death), urinary tract infection, febrile neutropenia, severe diarrhea, and acute hepatitis. The rate of serious infections in the ocrelizumab subgroup was consistent with the literature, although a higher rate was observed in the rituximab subgroup. A positive correlation was found between serious infectious complications and lower IgG levels. Additionally, longer exposure to anti-CD20 therapy in our cohort was associated with an increased risk of IgG deficiency and a higher incidence of serious infections. Lymphopenia was detected in 25 patients, though it was not directly linked to the occurrence of serious infections.ConclusionOur work confirms the tolerability and safety of anti-CD20 drugs in a real-world clinical practice MS cohort, despite their frequent association with analytical changes such as lymphopenia and hypogammaglobulinemia. To better understand the clinical significance of hypogammaglobulinemia secondary to anti-CD20 treatment and to develop strategies for mitigating the associated potential infection risk, future studies with larger populations are essential.